2018
DOI: 10.22201/ib.20078706e.2018.2.2127
|View full text |Cite
|
Sign up to set email alerts
|

Ecología alimentaria del tepezcuintle (Cuniculus paca) en áreas conservadas y transformadas de la Selva Lacandona, Chiapas, México.

Abstract: Ecología alimentaria del tepezcuintle (Cuniculus paca) en áreas conservadas y transformadas de la Selva Lacandona, Chiapas, México Foraging ecology of lowland paca (Cuniculus paca) in preserved and transformed areas of the Lacandon rainforest, Chiapas, Mexico

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…However, when comparing daily activity, the result was the other way around, with greater average overlap occurring in the case of L. platypus than in the case of P sapota. In relation with our second prediction, in which we were expecting to find greater activity overlap in species pairs including primarily frugivorous mammalian species than in those including the species with more generalist feeding habits (i. e., white-nosed coati), we found that the pair of species having the greatest overlap (delta 1 ≥ 0.67) in their daily activity patterns, in both tree species, was indeed constituted by the highly frugivore mammals paca and tapir (Naranjo 2009;Martínez-Ceceñas et al 2018). Moreover, we found that coatis (the species with the more generalist feeding habits) had in most of the cases a low degree of overlap in their daily activity with the other mammal species feeding on the fruits of the focal tree species but, in 3 out 8 paired comparison this overlap was relatively high (delta 1 ≥ 0.29).…”
Section: Discussionsupporting
confidence: 66%
“…However, when comparing daily activity, the result was the other way around, with greater average overlap occurring in the case of L. platypus than in the case of P sapota. In relation with our second prediction, in which we were expecting to find greater activity overlap in species pairs including primarily frugivorous mammalian species than in those including the species with more generalist feeding habits (i. e., white-nosed coati), we found that the pair of species having the greatest overlap (delta 1 ≥ 0.67) in their daily activity patterns, in both tree species, was indeed constituted by the highly frugivore mammals paca and tapir (Naranjo 2009;Martínez-Ceceñas et al 2018). Moreover, we found that coatis (the species with the more generalist feeding habits) had in most of the cases a low degree of overlap in their daily activity with the other mammal species feeding on the fruits of the focal tree species but, in 3 out 8 paired comparison this overlap was relatively high (delta 1 ≥ 0.29).…”
Section: Discussionsupporting
confidence: 66%
“…They have large home ranges that include water bodies (50–200 Ha) (Gutierrez et al, 2017 ; Harmsen et al, 2018 ) and occupy cavities to rest during the day (Figueroa-de-Leon et al, 2016 ). Paca consume a range of vegetation, including fruits from more than 20 tree species, and adapt their diet to the available species in their location (Martinez-Cecenas et al, 2018 ). Paca reach sexual maturity around 4 months of age and tend to give birth to a single mature offspring as early as 9 months old (El Bizri et al, 2019 ).…”
Section: Case Examplesmentioning
confidence: 99%
“…Na primeira ocasião, o indivíduo de C. paca retorna várias vezes para obter pedaços de vísceras de galinha e sai com eles em sua boca. Na segunda ocasião, como a carcaça do pombo estava amarrada, o indivíduo de C. paca desferiu diversas mordidas, retalhando os restos da ave. Na literatura referente à alimentação de C. paca, esse animal é considerado essencialmente frugívoro, consumindo frutos de diferentes espécies vegetais (ZUCARATTO et al, 2010;MARTÍNEZ-CECEÑAS et al, 2018). Foi encontrado na literatura registro de consumo de caramujos Pomacea por C. paca, ingeridos durante a época de vazante em rios amazônicos, o que indica, possivelmente, um comportamento oportunista (AQUINO et al, 2009).…”
Section: Resultsunclassified